Pentingnya Peran Kepuasan Kerja sebagai Jembatan antara Kualitas Hubungan Pemimpin-Anggota dengan Komitmen Organisasional - Ayu Widiantari, Ni Putu Natih; Utomo, Kabul Wahyu; Wibowo, Martino (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this study is to examine the impact of the quality of leader-member exchange towards organizational commitment with job satisfaction as an intervening variable on employees of The Central Statistics Office (BPS) in Bali. This study collects primary data via a self-enumerated questionnaire with 7-points Likert scale ranging from